2016
DOI: 10.1007/s10637-015-0320-9
|View full text |Cite
|
Sign up to set email alerts
|

A dose escalating phase I study of GLPG0187, a broad spectrum integrin receptor antagonist, in adult patients with progressive high-grade glioma and other advanced solid malignancies

Abstract: SummaryBackground Integrin signaling is an attractive target for anti-cancer treatment. GLPG0187 is a broad spectrum integrin receptor antagonist (IRA). GLPG0187 inhibited tumor growth and metastasis in mouse models. Methods We aimed to determine the Recommended Phase II Dose (RP2D) and to assess safety and tolerability of continuous i.v. infusion in patients with advanced malignant solid tumors. Anticipated dose levels were 20, 40, 80, 160, 320, and 400 mg/day in a modified 3 + 3 design. Plasma concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 30 publications
(32 reference statements)
1
33
0
Order By: Relevance
“…GLPG0187 showed anti-tumor activity in preclinical models of breast and prostate cancer [119], as well as effectiveness against glioma cells [66]. Preliminary results of the phase Ib study confirmed a favorable toxicity profile of the drug and early signs of clinical response in patients with progressive high-grade glioma and other solid tumors [120].…”
Section: Interfering With Integrin Signaling As a Therapeutic Strategmentioning
confidence: 81%
“…GLPG0187 showed anti-tumor activity in preclinical models of breast and prostate cancer [119], as well as effectiveness against glioma cells [66]. Preliminary results of the phase Ib study confirmed a favorable toxicity profile of the drug and early signs of clinical response in patients with progressive high-grade glioma and other solid tumors [120].…”
Section: Interfering With Integrin Signaling As a Therapeutic Strategmentioning
confidence: 81%
“…Aside from cilengitide, there are a number of αvβ3-targeted strategies in development for GBM, including GLPG0187, a small molecule antagonist of multiple integrins including αvβ3, αvβ5, αvβ6, and α5β1 (Cirkel et al, 2016), as well as approaches that use RGD peptides for αvβ3-targeted delivery of radionuclides (Jin et al, 2017), siRNA (He et al, 2017), and chemotherapy-loaded nanoparticles or nanogels (Chen et al, 2017; Fang et al, 2017). Considering that Glut3 addiction is also a feature of GBM cancer stem cells (Flavahan et al, 2013), targeting this phenotype with an αvβ3 antagonist has the potential to eradicate the most aggressive and drug resistant subpopulation within the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, substantial preclinical evidence suggests that pharmacological targeting of αvβ3 integrin effectively prevents metastatic colonization of the bone . Clinical trials using neutralizing antibodies and small molecule inhibitors against αvβ3 have shown promise; however, these have not specifically focused on bone metastasis . Microenvironmental factors such as TGFβ and VEGF have also been identified as potential therapeutic targets to prevent bone metastasis .…”
Section: Bone Metastasis Therapiesmentioning
confidence: 99%